Depression Levels and CD4 Counts in HIV Patients at Dr. Saiful Anwar General Hospital Malang - Budiarti, Niniek; Patra Utama, Haniel; Agustin Purwantiningrum, Danik; Dwiastuti Wisnu Putri, Winarni Dian (Jurnal Kedokteran Brawijaya, 2025)
Untreated depression in HIV patients is associated with lower CD4 cell counts attributed to the excessive HPA axis activity, which leads to increased cortisol secretion. This can accelerate the progression of HIV through shifting cytokine production from Th1 to Th2, which triggers CD4 cell destruction and stimulates HIV replication. This study aimed to determine the relationship between depression levels and CD4 counts in HIV patients at Dr. Saiful Anwar General Hospital Malang. This study used a quantitative method with an analytical observational study design and a cross-sectional approach. A total of 30 participants were selected through purposive sampling. The Beck Depression Inventory-II (BDI-II) questionnaire was used to evaluate the participants' depression levels. Six participants were identified with moderate depression, while 24 participants exhibited either no depression or minimal depression. The Spearman's Rank Correlation Coefficient test showed p=0.183, p>0.05, with a correlation coefficient of -0.250, indicating no significant relationship between the depression levels and CD4 cell count in HIV patients at Dr. Saiful Anwar General Hospital Malang. Nevertheless, among the study subjects with moderate depression (6 participants), low CD4 counts (≤345cells/mm3) were observed, suggesting a tendency for depression levels to be associated with CD4 count.